Techno-Economic Study of Biodiesel Generation from Sterculia foetida Seeds - Bilqist Imeilia Az Zahra; H.C. Theofany; Teuku Meurah Indra Riayatsyah; H.B. Aditiya; Bidattul S Zainal (Sustainable in Energy Science and Technology, 2025)
As fossil fuel reserves diminish and energy demand grows, biodiesel from non-edible oils has emerged as a promising renewable alternative. This study evaluates the feasibility of producing biodiesel from Sterculia foetida (Java olive) seeds, which contain 50–60 % oil. A second-generation biodiesel plant is designed and simulated using SuperPro Designer, covering oil extraction, transesterification, product purification, and by-product recovery. The plant processes 4,396 kg of seeds per hour in Lombok (Indonesia). Material and energy balances indicate nearly complete conversion to biodiesel, yielding ~16.19 million kg/year with a 0.001 % mass balance error. The total utility power demand is 6.2 million kWh/year, with the transesterification reactor consuming ~27 %. Economic evaluation (2021 USD) shows a capital investment of ~$3.82 million and annual operating cost of ~$20.72 million. At a biodiesel price of $1.00/L, annual revenue is ~$21.47 million, including ~$2.4 million from glycerol and co-products. Profitability metrics are positive: gross margin 3.48 %, ROI 19.67 %, payback period 5.08 years, IRR 9.14 %, and NPV ~$1.03 million. Sensitivity analysis shows profitability is most affected by biodiesel market price and feedstock cost. Overall, biodiesel production from Sterculia foetida is technically feasible and economically viable, diversifying Indonesia’s biodiesel feedstocks.